The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1099/ijs.0.061085-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesoflavibacter aestuarii sp. nov., a zeaxanthin-producing marine bacterium isolated from seawater

Abstract: An orange, rod-shaped, Gram-reaction-negative, aerobic and gliding bacterial strain devoid of flagella, designated strain KYW614(T), was isolated from seawater collected from Gwangyang Bay, Republic of Korea. Zeaxanthin was the major carotenoid pigment produced and flexirubin-type pigments were not produced. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain KYW614(T) belonged to the family Flavobacteriaceae and it was most closely related to Mesoflavibacter zeaxanthinifaciens TD-ZX30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Mesoflavibacter (Asker et al, 2007) appeared as paraphyletic in GBDP tree (Figure 8) because the type species of the genus, M. zeaxanthinifaciens (Asker et al, 2007), along with M . sabulilitoris (Park et al, 2014) were more closely related to Olleya (Nichols et al, 2005) than to M. aestuarii (Lee J. H. et al, 2014). When M. aestuarii and M .…”
Section: Resultsmentioning
confidence: 99%
“…Mesoflavibacter (Asker et al, 2007) appeared as paraphyletic in GBDP tree (Figure 8) because the type species of the genus, M. zeaxanthinifaciens (Asker et al, 2007), along with M . sabulilitoris (Park et al, 2014) were more closely related to Olleya (Nichols et al, 2005) than to M. aestuarii (Lee J. H. et al, 2014). When M. aestuarii and M .…”
Section: Resultsmentioning
confidence: 99%
“…Mameliella play important roles in the degradation of aromatic compounds 41,42 and can accumulate beneficial poly-β-hydroxybutyrate (PHB) granules in cells 43 . Mesoflavibacter can produce zeaxanthin that have strong antioxidant and anticancer properties 44,45 . Interestingly, based on the KEGG pathway analysis, “nitrotoluene degradation” and “methane metabolism” were increased in the three SA groups, which indicated that dietary RS contribute to the enrichment of the beneficial bacteria that are involved in degrading toxins and producing beneficial metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, one further species of the genus Mesoflavibacter, Mesoflavibacter aestuarii, was described from seawater collected from the South Sea of South Korea (Lee et al, 2014). Phylogenetic analyses based on 16S rRNA gene sequences showed that the genus Mesoflavibacter belongs to the family Flavobacteriaceae of the phylum Bacteroidetes (Asker et al, 2007;Lee et al, 2014).…”
mentioning
confidence: 99%
“…that strain GJMS-9 T is a member of the genus Mesoflavibacter (Table 2, Fig. S1; Asker et al, 2007;Lee et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation